Designing Nanoparticle-based Drug Delivery Systems for Precision Medicine - Yang , Jianhua; Jia , Chengyou; Yang , Jianshe (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
Traditional drugs are facing bottlenecks of lower solubility, absorption, and especially the inefficient organs or cells targeting during the precision medicine era. It is urgently needed to discover and establish new methods or strategies to modify old drugs or create new ones against the above defects. With the support of nanotechnology, the solubility, absorption and targeting of traditional drugs were greatly improved by modifying and fabricating with various types of nanoparticles to some extent, though many shortages remain. In this mini-review we will focus on advances in several most commonly used nanoparticles, from their nature and design, to drug delivery system and clinical application, that they overcome heterogeneous barriers in precision medicine, thereby ultimately improve patient outcome overall.